PRICAI 2018 : trends in artificial intelligence : 15th Pacific Rim International Conference on Artificial Intelligence, Nanjing, China, August 28-31, 2018, Proceedings.: trends in artificial intelligence : 15th Pacific Rim International Conference on Artificial Intelligence, Nanjing, China, August 28-31, 2018, Proceedings. Part II (2018) - Unknown
No abstract available